Triângulos pitagóricos, ternos pitagóricos e suas propriedades - COSTA, Eliel de Araujo e Silva (2019)
The present work is devoted to the study of the Pythagorean triangles, as well as the suits of numbers representing their sides, their algebraic and geometric form. Some of their properties, how they present themselves, and how to recognize these suits, are also presented to the generating formula of both primitive and non-primitive Pythagorean suits, and a consequence of this formula is that the triangles obtained through it are rectangles. To prove that there are infinite primitive Pythagorean suits through a variation of the formula quoted above and consequently infinite primitive Pythagorean triangles. Applying the concepts, lemmas and properties studied on the Pythagorean suits in this work in a particular case of Fermat's theorem. But before we speak a little of the historical context and about the mathematician who gives the name to this class of triangles, who was Pythagoras? It also addresses the discovery of a stone tablet from the Babylonian period and with it discover that before Pythagoras these triangles were already known and studied by the Babylonians, to present basic concepts on triangles and a demonstration of the Pythagorean Theorem.